PENGARUH LEVERAGE, KESEMPATAN BERTUMBUH DAN UKURAN PERUSAHAAN TERHADAP KOEFISIEN RESPON LABA - Alifiana, Meita; Praptiningsih, Praptiningsih (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2016)
This study aims to examine the variables of leverage, growth opportunities and the size of the companies that influence the earnings response coefficient. The purpose of the research is to empirically test the influence of Leverage, Growth Opportunities and Firm Size towards Earnings Response Coefficient. This research used 60 property & real estate companies listed on the Indonesia Stock Exchange in 2012-2014. The sampling technique used in this research was purposive sampling, based on criteria there are 35 companies and tested with multiple regression analysis. The type of data used is secondary data obtained from www.idx.co.id and www.yahoo.finance.com. These result indicate that that Leverage, Growth Opportunities and Firm Size has no significant effect on the Earnings Response Coefficient. The ability of independent variables (Leverage, Growth Opportunities and Firm Size) in explaining the dependent variable (Earnings Response Coefficient) is 0,9%. The remaining 99,1% is explained by another variables such as systematic risk, earning persistance, profitability, voluntary disclosure, auditor quality and others.